KONSEP PERMUKIMAN KEMBALI PADA KAWASAN KUMUH SUNGAI BANGER, PROBOLINGGO - Nareswarananindya, Nareswarananindya; Ramadhani, Annisa Nur (Unika Santo Thomas, 2023)
The Banger River has been converted into a high-density slum dwelling. Most of the slum dwellings are permanent buildings located above the river and around the river border, resulting in experiencing a significant decline in the quality of its facilities and infrastructure. The condition of buildings and infrastructure supporting slums in the Banger river area is analyzed with seven slum parameters according to the Ministry of Public Works Regulation No. 2 of 2016 Article 4 paragraph 2. The typology based on the geographical location categorized the Banger River area as slum dwellings on the edge of water bodies. The formulation of the problem that will be discussed in this study is to identify the physical and non-physical problems that affect the function of the Banger River area. The purpose of this study is to develop a pattern of slum settlements renewal that can optimize the potential and answer the problems that exist in the area. The research method chosen was descriptive qualitative with literature studies and field surveys. The results showed that the appropriate treatment concept was resettlement so that it could optimize the potential and could answer the problems of the seven slum parameters.